Practice nurses and cervical screening: A two‐country review. Issue 1 (28th June 2013) - Holmes, Colin; Mills, Jane; Chamberlain‐Salaun, Jennifer
<x xml:space="preserve">Abstract</x> The aim of this review is to explore the literature relating to the delivery of cervical screening by practice nurses (PNs) in the United Kingdom and Australia. Research relating to PNs began in earnest approximately 15 years ago in the UK context, and more recently, c.2005, in Australia. Although there is scant literature devoted specifically to the role of PNs in cervical screening, literature relating to the role of PNs provides evidence of the extent to which PNs in the United Kingdom and Australia are involved in the provision of cervical screening services. Findings from this review indicate that the role of PNs in the provision of cervical screening differs substantially between the United Kingdom and Australia. PNs in the United Kingdom provide a high percentage of cervical screening services, whereas in Australia general practitioners provide around 80% of all cervical smears, which account for only 0.6% of all procedures undertaken by PNs. Employment and funding models and inadequate multidisciplinary collaboration are contributing to the underutilization of PNs in Australia.